Beyond Violence: Religious Sources of Social Transformation in Judaism, Christianity, and Islam by James L. Heft, S.M. (New York: Fordham University Press, 2004. 162 pages.) (American Journal of Islam and Society, 2006)
This book contains six essays presented at an international conferenceentitled “Beyond Violence: Religious Sources of Social Transformation.” It brings together academic and activist Jews, Christians, and Muslims toexplore the potential of each religious tradition as a source of peaceful socialtransformation. The book thus problematizes the assumption that violence isminimized by excluding religion from public life.The book appropriately opens with Charles Taylor’s (McGill University)paper, which draws heavily on the thoughts of French philosopher ReneGirard Violence and the Sacred (Baltimore: The Johns Hopkins UniversityPress: 1979). Taylor explores the modes of transition of violence from purifyingkilling with metaphysical roots to political “categorical violence,”which makes ethnic cleansing possible. He gives a tripartite solution to violence:building ordered democratic polities that are likely to be less violent,spreading the benefits of such a society widely to prevent the formation ofdesperate excluded groups, and denouncing the self-righteous reconstitutionof violence for revenge by those who have suffered. These first two solutionsinvolve political and economic correctives at the governmental level,which may not hold true in the face of evidence. For example, violencecould be caused by a most democratic polity that finds no incentive to spreadits benefits, even to the most desperate of its own people. Taylor’s third solution,however, can resonate on a very personal level with many who, as aresult of suffering, feel entitled to revenge. It is forgiveness, he argues, anda recognition of a common, flawed humanity that may suppress the madnessof revenge and violent categorization (pp. 38-40) ...